THE DIGITAL LEARNING REVOLUTION: UTILIZING EDUCATION PLATFORMS IN THE SELF-CURRICULAR AGE - Novianty Djafri; Syamsu Qamar Badu, Mardia Bin Smith (Adisam Publisher, 2024)
The digital age has brought significant transformations in many aspects of life, including in the education sector. The digital education revolution, especially in the implementation of online learning platforms, has opened wide doors to self- learning and lifelong learning. The aim of this research is to explore how digital education platforms affect the learning process and identify the benefits and challenges that arise from its implementation. Using a qualitative approach through literary research methods, the study collects and analyzes data from various related sources to gain a comprehensive understanding of this phenomenon. The findings show that despite some challenges, such as accessibility and digital disparity, the widespread implementation of digital learning platforms provides more equitable educational opportunities, encourages self-learning, and prepares students with skills relevant to the digital age.